Governança corporativa nas sociedades cooperativas brasileiras - Schardong, Ademar (Universidade do Vale do Rio dos Sinos, 2020)
Based on the characteristics of cooperative societies, this dissertation discusses the opportunities for implementing a referential model of corporate management that preserves its specificities. Exploratory research, through analysis of the legislation which covers the various corporate types admitted under Brazilian law, the text books related to the interpretation of legal instruments and the comparison with the practices adopted by the capital companies, was used to understand and interpret the current models. The analysis evaluated the representativeness of the members in the general meetings, the qualification of the members of the governance bodies and the form of their constitution, composition, segregation of functions and their attributions. The characteristics of cooperative societies, as non-profit corporations, relating to the formation of capital, the right to one vote per shareholder regardless of the value of the paid-in shares, composition of management and supervisory bodies by members and the distribution of net result, proportion of operations, requires specific treatment in the corporate governance structure. These do not preclude the adoption of good practices, in line with those adopted by capital companies, in line with the recommendations of regulators and stakeholder demands regarding the principles of equity, compliance and transparency. In conclusion, it can be said that a corporate governance model of its own is feasible for cooperative societies, subsuming the recommendations of good practices adopted by the capital companies, without harming the specific characteristics deriving from the specific corporate legislation.
Keywords: Sociedades cooperativas; Modelo de governança cooperativa; Princípios cooperativos; Cooperative Societies; Cooperative governance model; Cooperative Principles; ACCNPQ::Ciências Sociais Aplicadas::Direito